"Dieu" ou "démon" de Socrate ? Augustin contre Apulée - Saudelli, Lucia (Revue d'études augustiniennes et patristiques, 2014)
This study focuses on Augustine’s polemic against Apuleius about Socrates’ daemon. At first it examines the Augustinian text in order to clarify the goal, strategy and philosophical implications of this polemic, as well as its specificity and limits: the question raised by Augustine about the nature of the Socratic daemon; the link he establishes between daemons and theatre, which, according to him, goes back to Plato; the distinction between god and daemon that he ascribes to Apuleius. Afterwards the study treats the problem of the mediation between the divine and the human from both Christian and Platonic perspectives, explaining why, in Augustine’s thought, Jesus Christ replaces the daemons as the only true Mediator. Finally it shows that Augustine separates Socrates from Platonic philosophers by attributing to him a monotheistic doctrine, and it inquires about the Socratic thought itself.